More than just routine: Examining the disproportionate impact of police stops among Indigenous Americans - Campagna, Lena M. (Journal of ethnicity in criminal justice, 2024)
Although research shows that Indigenous peoples are disproportionately represented in the criminal justice system, little is known about the nature of police contacts and Indigenous Americans’ perceptions of legitimacy. This study uses data from the Police Public Contact Survey to determine whether Indigenous Americans are more likely to experience traffic stops relative to other racial and ethnic groups and the extent that Indigenous Americans assess traffic stops as “legitimate.” Results indicated the odds that Indigenous Americans experienced traffic stops were greater than all other racial groups—with significant differences relative to White, Black, Hispanic, and Asian participants. Indigenous Americans were also more likely to perceive traffic stops as illegitimate, even after controlling for officer characteristics and stop outcomes.